Pemetaan Lahan Dan Hasil Pertanian Dengan Metode Query Spatial Berbasis GIS (Sistem Informasi Geografis) Dinas Pertanian Kabupaten Manggarai - Beatinus Brianevant Frananta Sitepu; Arita Witanti (Universitas Mercu Buana Yogyakarta, 2023)
Indonesia is considered an agricultural country because agriculture is a strategic sector that impacts national economic growth. Agricultural products in Indonesia are influenced by geographical factors such as mountainous areas or highlands; usually, agricultural products are more dominant in vegetables and leaves. Meanwhile, for lowland areas, the type of agriculture is usually dominated by rice, secondary crops, soybeans, and grains and spices. Based on the types of agriculture above, there are differences in agricultural commodities due to differences in geographical location between the highlands and lowlands. Therefore, it is necessary to have a breakthrough in a system that can map the area based on the availability of land and types of agricultural commodities to monitor agricultural activity, especially in the Manggarai Regency agricultural office, which is currently trying to boost agricultural products. There seems to be no geographic information system for agricultural management in Manggarai Regency; thus, the researcher constituted the title